HUMAN-GEOGRAPHY ASPECTS OF INTEGRATED ASSESSMENT OF DEMOGRAPHIC SAFETY OF UKRAINE AND LVIV REGION - Гудзеляк, Ірина; Верчин, Наталія (Human Geography Journal, 2016)
A definition of "demographic safety" taking into account existing scientific approaches to understanding this category. On the basis of demographic safety that sattles accounts on basis of eleven indexes, described tendencies of demographic safety in Ukraine and Lviv region from 1990. Determined the spatial differences in demographic state of safety of Ukraine in 2013. The comparative analysis of the main demographic indicators of demographic safety of Ukraine and some European countries. The measures to enhance demographic safety and regions.